Collapse performance assessment of steel moment frames designed to Eurocode 8. (August 2021) - Macedo, L.; Castro, J.M.
Highlights: Safety margins against collapse of steel moment frames designed to Eurocode 8 are evaluated. 360 archetype buildings were designed according to EC8. Code-prescribed and improved behaviour factors were adopted. Moment-resisting frame buildings designed to EC8 exhibit acceptable safety margins against collapse. Abstract: This paper reports on a study performed on steel moment-resisting frame buildings with the aim of evaluating the safety margins against collapse of buildings designed according to Eurocode 8 (EC8) when subjected to maximum considered earthquake ground motions. To this end, the methodology proposed in FEMA P695 is employed. A set of 360 archetype buildings are designed according to EC8 using code-prescribed behaviour factors for medium and high ductility class structures. Additionally, behaviour factors determined according to an Improved Force-Based Design (IFBD) methodology are also adopted. IFBD allows for a more rational selection of the behaviour factor and is fully compliant with the EC8 prescriptions. The results from the seismic performance assessment of the structures allow for an improved understanding of the seismic behaviour of steel MRFs designed according to EC8 and highlight the efficiency that is achieved with the adoption of the IFBD methodology, both in terms of reductions of steel weight as well as in terms of the consistency between the design assumptions and the ductility demand that is explored from the buildings. Moreover, the results also indicate that moment-resisting frame buildings designed according to EC8 are characterized by acceptable safety margins against collapse.